Determinants of organizational success: an empirical analysis of insurance sector in India - Vivek Srivastava, Dr. Adhip Kumar Mahanty, Dr. Sunil Kumar Pandey (International Journal of Advanced Science and Technology, 2020)
Successful performance of an organization depends on the extent of retention competitiveness of employees, which can be increased by making the input factors efficient and productive. Employee, being an utmost important factor for an organization, needs high concern. There are several facets through which an employee can be made efficient and productive, retention is one of them. This paper is an effort to find out the factors which are responsible for employee retention in insurance companies in India. An empirical study through factor analysis has been done by conducting a survey of 212 managers of insurance companies by applying convenience sampling method. This paper addresses the core factors of retention that are responsible for an insurance organization in retaining its dedicated employees.